2004
DOI: 10.1111/j.1468-3083.2004.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infection with Trichophyton mentagrophytes varietas interdigitale on phagocytosis in humans

Abstract: This investigation confirms the defect in the function of phagocytes of patients chronically infected by T. m. var. interdig. Terbinafine was shown to be an effective antimycotic drug, both fungicidal and immunostimulative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…It is generally accepted that the efficient system of phagocytic cells is one of the basic mechanisms of non-specific cellular antimycotic immunity involved in the elimination of dermatophytes. Two different mechanisms are engaged in fungal spores destroyed by granulocytes: the first is connected with oxygen-dependent killing and the second mechanism is connected with enzymatic digestion in lysosomes (10,15,18). The results of the present investigation confirm that the mechanism of oxygen-dependent killing is crucial in infections caused by T. mentagrophytes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It is generally accepted that the efficient system of phagocytic cells is one of the basic mechanisms of non-specific cellular antimycotic immunity involved in the elimination of dermatophytes. Two different mechanisms are engaged in fungal spores destroyed by granulocytes: the first is connected with oxygen-dependent killing and the second mechanism is connected with enzymatic digestion in lysosomes (10,15,18). The results of the present investigation confirm that the mechanism of oxygen-dependent killing is crucial in infections caused by T. mentagrophytes.…”
Section: Discussionsupporting
confidence: 75%
“…It could be assumed that a decrease or increase in phagocytic activity and oxygen metabolism indices may be somehow related to the progress of infection and suppressive interaction of the fungus, the elimination of which during recovery caused significant increases in investigated indices of non-specific immunity (5,6,13,23). The suppressive effect on cellular non-specific antimycotic mechanisms is caused by mannans which are embedded in cell walls of dermatophytes (2,8,9,10,12). The inhibiting role of these substances is probably blocking surface receptors of phagocytic cells (4,12,15,21).…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytes released toxic enzymes and kill fungal elements by ingestion and digestion. In one study, phagocytosis was found to be altered in all patients with chronic trichophytosis [6]. There is no consensus as to whether immune responses play a key role in dermatophytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatophytes, mostly Tr. rubrum, possibly produce various mycotoxins, some of which can exert an immunosuppressive activity, favoring the chronicity of infection [6,7].…”
Section: Discussionmentioning
confidence: 99%